Rantai Nilai Agribisnis Komoditas Singkong Berbasis Kearifan Lokal dan Strategi Pengembangannya di Kampung Adat Cireundeu - Rohayati Suci Indrianingsih; Tita Nurmalinasari Hidayat; Yayang Ade Suprana (LPPM Universitas Malikussaleh - Indonesia, 2026)
Cireundeu Traditional Village is recognized for its utilization of cassava as an alternative in food diversification efforts and in sustaining local food security. Despite this potential, the existing cassava agribusiness system remains inefficient, leading to suboptimal economic returns. This study aims to map the cassava agribusiness value chain and formulate strategies for its development in Cireundeu Traditional Village. The research was conducted from August to October 2025 in Cireundeu Traditional Village, Leuwigajah, Cimahi City, employing a mixed-method approach that included in-depth interviews, observations, documentation, and surveys. The collected data were analyzed using value chain and SWOT analyses. Findings indicate that the cassava agribusiness value chain structure in Cireundeu Traditional Village is still relatively simple, as most marketing activities are centered on the local market. The main actors in the value chain consist of farmers, processors of semi-finished cassava products, custom-based MSMEs, producers of finished goods, as well as retailers and resellers. The development of cassava agribusiness in this area can be pursued through strategies such as enhancing production technology capacity and strengthening digital-based promotion efforts.